Confusions and responses of managerial public health nurses during the COVID‐19 pandemic in Japan. Issue 1 (9th November 2021) - Honda, Chikako; Sumikawa, Yuka; Yoshioka‐Maeda, Kyoko; Iwasaki‐Motegi, Riho; Yamamoto‐ Mitani, Noriko
Abstract: Objective: This study aimed to elucidate the experiences of public health nurses (PHNs) in Japan during the first wave of COVID‐19. Design and sample: Twelve PHNs in charge of responding to COVID‐19 in X‐city within Tokyo metropolis in Japan participated in this case study. Measurements: Data were collected through self‐administered questionnaires and semi‐structured interviews on PHNs' experiences from January 2020 to May 2020. Results: Initially, only infectious disease control division (IDCD) PHNs experienced confusion due to the rapidly increased workload. Managerial PHNs attempted to explain the need for a dispatch system for the IDCD, using available statistical data from other managerial members, within one's maximum understanding of this unprecedented situation. Without having a clear and forward‐looking understanding regarding the purpose and reasons for dispatching, some dispatched PHNs had concerns and frustrations; they did not view the COVID‐19 pandemic as a disaster. In the never‐ending, exhausting work, PHNs managed to modify the provision of conventional services to residents. Conclusions: Despite experiencing confusion, PHNs worked to continuously provide community services, re‐considering the meaning of public health nursing. Prioritizing the work and shifting tasks to other professionals at an early stage of the pandemic may prevent organizational dysfunction.